PENGARUH DISIPLIN, KOMITMEN ORGANISASI DAN FASILITAS BELAJAR TERHADAP KEPUASAN GURU SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 1 MANYAK PAYED KABUPATEN ACEH TAMIANG - Santi Novrida (Universitas Islam Islam Sumatera Utara, 2020)
The superiority of a nation is no longer based on natural resources alone, but on the excellence of human resources, one of which is educators who are able to answer challenges very quickly. Education is basically an effort to develop human resources, although efforts to develop human resources are not only carried out through education, especially formal education or schools, but until now, education is still seen as a means and vehicle for developing human resources that is carried out systematically , programmatic, and tiered. Discipline is an attitude, behavior and actions that are in accordance with company regulations both written and unwritten. The regulation in question includes absenteeism, slow entry, and quick return of employees. So this is an indisciplinary attitude that needs to be addressed properly by the management (School). Many interpret this discipline when employees always come and go home on time. That opinion is only one of the demands of management. Therefore, discipline can be interpreted as written or unwritten behavior. From the results of the identification of the problems above, the following problems can be formulated: How does Discipline influence Teacher Satisfaction in SMPN I Payet's Aceh Tamiang District. Performance = 10.868 C +, 227 X1 +, 090 X2 +, 402 X3 Based on the results of the equation, the following explanation can be described: Constant value of 10.868 means that if the overall value of the variable (SinismeX1, Emotional IntelligenceX2, Work StressX3) increases respectively of 1a, the value of Performance (Y) will rise to 10.868. The value of the Cynic coefficient of 0.227 means that if the value of Cynicism increases by 1a, the value of performance will also increase by 0.227. Positive coefficient value means that Cynicism has a positive influence on Performance. The value of the Emotional Intelligence coefficient of 0.090 means that if the Emotional Intelligence value increases by 1a, the performance value will also increase by 0.090. A positive coefficient value means that Emotional Intelligence has a positive influence on Performance. The value of the Job Stress coefficient of 0.402 means that if the value of Job Stress rises by 1a, the performance value will also increase by 0.402. A positive coefficient value gives the meaning that Job Stress gives a positive influence on Performance.